2017
DOI: 10.1111/tbed.12748
|View full text |Cite
|
Sign up to set email alerts
|

Inferring within-herd transmission parameters for African swine fever virus using mortality data from outbreaks in the Russian Federation

Abstract: SummaryMortality data are routinely collected for many livestock and poultry species, and they are often used for epidemiological purposes, including estimating transmission parameters. In this study, we infer transmission rates for African swine fever virus (ASFV), an important transboundary disease of swine, using mortality data collected from nine pig herds in the Russian Federation with confirmed outbreaks of ASFV. Parameters in a stochastic model for the transmission of ASFV within a herd were estimated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(119 citation statements)
references
References 42 publications
(76 reference statements)
6
109
2
2
Order By: Relevance
“…Overall, Q=728/Δt static multilayer networks were constructed for each value of Δt considered. In this study, Δt=7 days and Δt=28 days were considered for constructing networks, since these represent a range of likely farm‐level infection period that would precede the detection of important swine diseases (such as ASF, CSF and FMD), thus preceding the implementation of disease control activities (Guinat et al, ; Porphyre et al, ). As such, for each scenario considered, 104 and 26 multilayer networks were constructed when Δt=7 days and Δt=28 days, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, Q=728/Δt static multilayer networks were constructed for each value of Δt considered. In this study, Δt=7 days and Δt=28 days were considered for constructing networks, since these represent a range of likely farm‐level infection period that would precede the detection of important swine diseases (such as ASF, CSF and FMD), thus preceding the implementation of disease control activities (Guinat et al, ; Porphyre et al, ). As such, for each scenario considered, 104 and 26 multilayer networks were constructed when Δt=7 days and Δt=28 days, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…To calculate R 0 the number of infected animals for each time step (i.e., day) is needed, but these data are virtually impossible to obtain for a wild population. However, for diseases with a high case-lethality ratio, mortality cases can be used as a proxy for the number of newly infected individuals (e.g., [11]). Once appropriate data on carcasses are collected, several mathematical methods can be used to estimate R 0 value [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, during calendar year 2017, the Foreign Animal Disease Diagnostic Laboratory (FADDL) at Plum Island Animal Disease Center performed only two cases requesting ASF testing and both were negative (Personal communication). Of note, however, a stochastic model used to evaluate transmission of ASFV within a population found that the virus may be circulating in a herd for several weeks before a marked increase in mortality is observed, which limits the usefulness of mortality data as a means of early detection in an outbreak scenario ( 105 ). It may also be useful to compare the conditions in the United States to those in Europe to determine whether the buffer zones necessary to quell an ASF outbreak in Europe ( 90 ) would be similar to those required for an outbreak in the United States.…”
Section: Discussionmentioning
confidence: 99%